2011
DOI: 10.1002/jcp.22423
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium release activated calcium channels in osteoclast differentiation

Abstract: Osteoclasts are specialized macrophage derivatives that secrete acid and proteinases to mobilize bone for mineral homeostasis, growth, and replacement or repair. Osteoclast differentiation generally requires the monocyte growth factor m-CSF and the TNF-family cytokine RANKL, although differentiation is regulated by many other cytokines and by intracellular signals, including Ca2+. Studies of osteoclast differentiation in vitro were performed using human monocytic precursors stimulated with m-CSF and RANKL, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 31 publications
5
46
2
Order By: Relevance
“…In regard to the genetic interaction of Trpc1 and I-mfa in osteoclastogenesis, we propose that maximal and/or persistent activation of I CRAC /I SOC through TRPC1 in cells lacking I-mfa leads to excessive osteoclastogenesis and reduced bone mass. This suggestion is supported by our experiments in myeloid precursors and in studies in Orai1 null mice showing similar but more severely defective osteoclastogenesis (51) and in vitro studies using Orai1-depleted osteoclasts (52,53). The more severe and nonspecific effect of the deletion of Orai1 in numerous cell types, including osteoclasts compared with TRPC1, is in agreement with Orai1 being a core component of the CRAC channel and TRPC1 being a regulatory protein whose function is dispensable for Orai1.…”
Section: Discussionsupporting
confidence: 83%
“…In regard to the genetic interaction of Trpc1 and I-mfa in osteoclastogenesis, we propose that maximal and/or persistent activation of I CRAC /I SOC through TRPC1 in cells lacking I-mfa leads to excessive osteoclastogenesis and reduced bone mass. This suggestion is supported by our experiments in myeloid precursors and in studies in Orai1 null mice showing similar but more severely defective osteoclastogenesis (51) and in vitro studies using Orai1-depleted osteoclasts (52,53). The more severe and nonspecific effect of the deletion of Orai1 in numerous cell types, including osteoclasts compared with TRPC1, is in agreement with Orai1 being a core component of the CRAC channel and TRPC1 being a regulatory protein whose function is dispensable for Orai1.…”
Section: Discussionsupporting
confidence: 83%
“…Next we considered the protein Stim1, which is an ER Ca 2+ sensor controlling Ca 2+ fluxes during osteoclastogenesis (16,17,25). We expressed Tmem178-HA and Stim1-Myc in HEK293T cells and found that Tmem178 and Stim1 interact in resting conditions (control), and to a less extent in the presence of Tg and Tg + 1.8 mM Ca 2+ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological inhibition of Stim1 impairs SOCE, thereby blocking osteoclastogenesis (16). In addition to associating with Orai1 to control SOCE, Stim1 also couples to numerous other Ca 2+ channels, Ca 2+ pumps, ER chaperone proteins, and regulatory adaptor proteins, thereby influencing multiple pathways of Ca 2+ transport (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative selection of B cells, which occurs in the bone marrow to prevent the generation of self-reactive cells and subsequent autoimmunity, is regulated by the selective activation of ERK signaling triggered by CRAC-dependent Ca 2+ signals (5). Although CRACs are not the only class of calcium channels expressed on osteoclasts, they are required for cell fusion, a late event in osteoclast differentiation (6). Because osteoclasts cannot function properly without multinucleation, selective CRAC inhibition may be useful in the management of hyperresorptive states in RA patients.…”
mentioning
confidence: 99%